2004
DOI: 10.1183/09031936.04.00121404
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preventing exacerbations on deterioration of health status in COPD

Abstract: Exacerbations of chronic obstuctive pulmonary disease (COPD) are associated with worse health status. The Inhaled Steroids in Obstructive Lung Disease in Europe (ISOLDE) study showed that treatment with fluticasone propionate (FP) reduced exacerbation frequency and the rate of deterioration in health status as compared with placebo. The present study analysed these data to test whether the effect of FP on health status was attributable to its effect on exacerbations.Rates of deterioration in St George9s Respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
222
4
13

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(250 citation statements)
references
References 24 publications
11
222
4
13
Order By: Relevance
“…Acute exacerbation of chronic obstructive pulmonary disease (COPD-AE) is a major cause of hospital admission and is associated with increased mortality, an impaired quality of life and higher health care expenditures (1)(2)(3). Randomized controlled trials have shown that noninvasive ventilation (NIV) reduces the need for endotracheal intubation, reduces complications and increases short-term survival in patients with COPD-AE (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Acute exacerbation of chronic obstructive pulmonary disease (COPD-AE) is a major cause of hospital admission and is associated with increased mortality, an impaired quality of life and higher health care expenditures (1)(2)(3). Randomized controlled trials have shown that noninvasive ventilation (NIV) reduces the need for endotracheal intubation, reduces complications and increases short-term survival in patients with COPD-AE (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Arthritis Glaucoma Bowel and prostate cancer In summary, there is a consensus now that both airway and systemic inflammation play a key role in the pathogenesis of chronic obstructive pulmonary disease 99,100,101 . The underlying mechanisms and interactions are likely to be complex and need better description which is an important future research goal 102 .…”
Section: Miscellaneousmentioning
confidence: 99%
“…Sobre este curso crónico aparecen episodios agudos de exacerbación, con un aumento de los síntomas habituales (disnea y limitación de la actividad física). Las exacerbaciones constituyen un problema frecuente en los pacientes con EPOC y se han asociado a disminución de la capacidad funcional, declinación acelerada de la función pulmonar, menoscabo del estado de salud y calidad de vida, siendo responsables de muchas admisiones hospitalarias, y de este modo incrementarían los costos de la atención de salud y el riesgo de muerte [10][11][12][13][14][15] . Las infecciones bacterianas y virales son la principal causa de las exacerbaciones de la EPOC, seguidas de la pobre adherencia al tratamiento, la contaminación ambiental, embolia pulmonar y otras causas menos prevalentes 16 .…”
unclassified